Penalaran Argumen Siswa dalam Teks Argumentatif untuk Meningkatkan Kemampuan Siswa dalam Berpikir Kritis - Permanasari, Dian; Atika, Eka; Salsabilla, Martinia Putri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
In an effort to improve the culture of critical thinking in high schools, this research aims to find argumentative reasoning techniques used by students in argumentative written discourse. This research uses a qualitative approach with a theoretical orientation in discourse analysis to achieve this goal. Discourse written by students is the data source for this research. This data comes from assignments given by teachers to students to write arguments. Therefore, this data collection method uses available student assignment documents. The research results obtained through the data analysis process show that students' argument reasoning methods in written argument discourse consist of: (1) arguments with examples, (2) arguments with authority, and (3) arguments with causes.